2021
DOI: 10.1111/1440-1703.12215
|View full text |Cite
|
Sign up to set email alerts
|

Assessing insect herbivory on broadleaf canopy trees at 19 natural forest sites across Japan

Abstract: We present the largest freely available herbivory dataset for Japan representing data collected from a network of 19 natural forest sites across the country. Sampled network sites were part of the Monitoring Sites 1000 Project organized by the Ministry of the Environment. Sites were located across a range of climate zones, from subarctic to subtropical, and broadleaf trees (both evergreen and deciduous) were targeted at each site. Litterfall traps were used to assess leaf damage caused by leaf‐chewing insects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Specifically, we showed that global warming will increase background herbivory in mature birch trees by decreasing tannin concentrations in the canopy. In contrast to mature birch trees (B. ermanii), an early successional species (pioneer), mature oak trees (Quercus crispula), a late successional species (climax), showed decreased herbivory in response to soil warming (Nakamura et al, 2014) and toward lower elevations (Takafumi et al, 2021). These combined results suggest that global warming is likely to decrease background herbivory in mature oak trees.…”
Section: Prediction Of Global Warming Effectsmentioning
confidence: 92%
“…Specifically, we showed that global warming will increase background herbivory in mature birch trees by decreasing tannin concentrations in the canopy. In contrast to mature birch trees (B. ermanii), an early successional species (pioneer), mature oak trees (Quercus crispula), a late successional species (climax), showed decreased herbivory in response to soil warming (Nakamura et al, 2014) and toward lower elevations (Takafumi et al, 2021). These combined results suggest that global warming is likely to decrease background herbivory in mature oak trees.…”
Section: Prediction Of Global Warming Effectsmentioning
confidence: 92%
“…EcoPlate data offer an opportunity for comparative studies among forest types and for testing community ecology and ecosystem function hypotheses at broad spatial scales (e.g., testing for a latitudinal gradient in multifunctionality in soil microbial communities and elucidating the relative importance of microbial communities in forest ecosystem function). The data can also be analyzed together with the results of associated projects in the same plots (e.g., tree census, Ishihara et al, 2011; litter fall, Suzuki et al, 2012; ground‐dwelling beetles, Niwa et al, 2016; tea bag decomposition, Suzuki et al, 2019; herbivory, Takafumi et al, 2021). Furthermore, if the EcoPlate is remeasured at the same plots in a few years or decades, we can assess the impact of recent climate change on soil microbial communities.…”
Section: Introductionmentioning
confidence: 99%